MECHANISMS FOR SHAPING THE LEGAL CULTURE OF YOUTH - Yuldashev , Shohruh (International Conference on Social Sciences & Humanities, 2026)
This article provides a scientific and theoretical analysis of the role of legal culture in the life of individuals and society, as well as its influence on citizens’ political and legal activity and the formation of electoral culture. The importance of subjective rights and civil, political, social, and economic rights in the development of legal culture is examined. Particular attention is paid to the negative impact of legal nihilism and legal romanticism on citizens’ legal consciousness, their trust in state institutions, and participation in democratic processes. Enhancing legal culture is regarded as an important factor in ensuring the conscious and responsible exercise of citizens’ electoral rights. Furthermore, the role of moral values, the family, the mahalla community, and various subcultural environments in shaping an individual’s legal consciousness, legal behavior, and legal values is substantiated.